Economic Effects of Environmental Taxation on Chemical Fertilizers in Korea - 김창길 (한국농촌경제연구원, 2007)
Environmental taxes as one of market-based instruments forces producers and consumers to consider the cost of negative externality in their economic decision. This paper analyzes the economic effects of environmental taxation on chemical fertilizers which is focused on effects of fertilizer consumption, rice yield, farmer's income, tax revenue from national economy aspect, enhancement of economic welfare through quality improvement of environment. The analytical results show that in order to achieve effective policy objective of the imposition of environment tax on chemical fertilizers very high tax rate is required due to inelastic demand of chemical fertilizer but it requires high cost burden on the part of farmers. This study provides an insight into the application of market-based instrument to achieve sustainable agricultural development.
Keywords: nonpoint pollutants; polluter-pays principle; internalization of negative externality; environmental taxation; yield-response function; nonpoint pollutants; polluter-pays principle; internalization of negative externality; environmental taxation; yield-response function